Altered functional connectivity in brain networks underlying self-referential processing in delusions of reference in schizophrenia. (30th May 2017) - Larivière, Sara; Lavigne, Katie M.; Woodward, Todd S.; Gerretsen, Philip; Graff-Guerrero, Ariel; Menon, Mahesh
Abstract: Delusions of reference in schizophrenia are thought to result from misattributions of self-relevance to neutral events. Activation of regions within the cortical midline structures (CMS; e.g., medial prefrontal cortex, cingulate cortex, and precuneus) have been previously associated with self-referential processing in schizophrenia patients; however, the specificity of this pattern to individuals with current delusions of reference has yet to be determined. In the present study, we identified functional brain networks that underlie self-referential processing using task-based multivariate functional connectivity. Healthy control subjects ( n =15) and schizophrenia patients with ( n =14) and without ( n =13) current delusions of reference were shown ambiguous statements while undergoing functional magnetic resonance imaging, and evaluated whether these statements were thought to be specifically about them. Our results revealed two functionally distinct CMS networks that differed between patients and controls during self-referential processing: a posterior CMS network, which showed muted deactivity in non-delusional patients; and an anterior CMS network, in which delusional patients demonstrated hyperactivity. Furthermore, activity within the anterior CMS network across the three groups showed a linear pattern of increasing activity associated with greater intensity of delusions of reference, suggesting that hyperactivity in this network may underlie delusions of reference. Highlights: We compared functional brain activity associated with self-referential processing in schizophrenia patients with and without current delusions of reference and healthy controls. Non-delusional patients showed reduced deactivity in the posterior CMS network whereas delusional patients showed hyperactivity in the anterior CMS network. Increasing activity within the anterior CMS network was associated with greater intensity of delusions of reference.